Plant growth regulators in poplar clones differing in resistance to the fungus Ceratocystis fimbriata Ell. et Haist - Jadwiga Stopińska (Acta Societatis Botanicorum Poloniae, 2014)
In poplar clones with different resistance to the fungus Ceratocystis fimbriata growth of shoots, intensity of transpiration and the level of endogenous growth regulators were determined. More resistant clones, Populus 'Robusta' and P. 'PK-136-2' (P. nigra 'Italica': x P. laurifolia) had more intensive growth of shoots, higher water content in leaves and a lower intensity of transpiration than the more susceptible clone, - P. 'NE-42' (P. maximowiczi x P. trichocarpa). The leaves of the more resistant clones contained more auxins (IAA) and cytokinins, especially zeatin, and less growth inhibitors (ABA) than those of the susceptible one. The level of plant growth regulators and/or the relations betweeen them may be responsible for the different poplar resistance to C. fimbriata.